Jurnal BUSINESS & ENTREPRENEURSHIP: an analysis on the decision model of smart plus insurence product purchase - Fitry primadona, Ujang sumarwan ; Mukhamad najib (SB-IPB, 2016)
tujuan penelitian ini menganalisis model keputusan pembelian produk asuransi smart plus